Problematika Pendidikan Agama Islam di Era Digital dan Media Sosial - Fitra Anisa; Vella Fitri Aulia; Herlini Puspika Sari (LPPI Yayasan Almahmudi bin Dahlan, 2026)
The development of information and communication technology in the digital age has brought about significant changes in various aspects of life, including in the field of education. Islamic Religious Education (IRE), as a subject that plays a role in shaping the character and spiritual values of students, also faces various challenges due to the rapid development of technology and social media. This article aims to analyse the various issues arising in the implementation of Islamic Religious Education in the digital and social media era. This study employs a qualitative method using a literature review approach, analysing various books, academic journals, and relevant literature sources pertaining to the research theme. The findings indicate that the digital age presents significant opportunities for the development of Islamic Religious Education through the use of technology as an innovative and interactive learning medium. However, various issues have emerged, such as low digital literacy among students, the dissemination of unverified religious information, a decline in control over social media use, and challenges for teachers in integrating Islamic values with technological advancements. Therefore, adaptive learning strategies are required, alongside the strengthening of digital literacy and moral values, to ensure that Islamic religious education continues to shape students of noble character who are wise in their use of technology in the digital age.